2006
DOI: 10.1073/pnas.0504777103
|View full text |Cite
|
Sign up to set email alerts
|

Prestressed F-actin networks cross-linked by hinged filamins replicate mechanical properties of cells

Abstract: We show that actin filaments, shortened to physiological lengths by gelsolin and cross-linked with recombinant human filamins (FLNs), exhibit dynamic elastic properties similar to those reported for live cells. To achieve elasticity values of comparable magnitude to those of cells, the in vitro network must be subjected to external prestress, which directly controls network elasticity. A molecular requirement for the strain-related behavior at physiological conditions is a flexible hinge found in FLNa and some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
392
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(435 citation statements)
references
References 41 publications
39
392
1
Order By: Relevance
“…We find that worms exhibit a rich mechanical response comprising an initial linear regime followed by nonlinear strain stiffening. This behavior is qualitatively similar to the results of many well-known experiments in biomechanics (12)-ranging from the mechanical response of a shark's skin (25) to the properties of cardiac muscle (27) and purified actomyosin networks (28). However, it is unusual to find such behavior at the whole-organism level, due to structural heterogeneities.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…We find that worms exhibit a rich mechanical response comprising an initial linear regime followed by nonlinear strain stiffening. This behavior is qualitatively similar to the results of many well-known experiments in biomechanics (12)-ranging from the mechanical response of a shark's skin (25) to the properties of cardiac muscle (27) and purified actomyosin networks (28). However, it is unusual to find such behavior at the whole-organism level, due to structural heterogeneities.…”
Section: Introductionsupporting
confidence: 85%
“…Thus, worms exhibit increasing effective stiffness with increasing applied stress, a phenomenon widely observed in soft matter, including other living materials (27,28,51).…”
Section: Structural Deformation Of Cells and Organellesmentioning
confidence: 97%
“…Differential splicing provides an alternate mechanism for producing FLN isoforms of altered biomechanical properties; FLNB can be differentially spliced so that only the hinge I region is excluded from the translated protein ). FLNA and FLNB respond similarly during in vitro rheological measurements showing resistance to 30-and 10-Pa shear stress, respectively, but in contrast, FLNA/B isoforms missing the first hinge region showed decreased elasticity in response to applied stress breaking at lower applied stress, 0.1 Pa, even though the cross-linking gelation concentration was equivalent to full-length FLN (Gardel et al 2006). The absence of hinge I also affects regulation of cross-linking by proteolysis since this hinge contains the calpain cleavage site (Gorlin et al 1990).…”
Section: Filamin Biomechanicsmentioning
confidence: 93%
“…FLN is the most powerful F-actin crosslinking protein characterised, requiring a minimal concentration to cause gelation with the threshold determined as a relative FLN:actin monomer molar concentration of ∼1:200 (Tseng et al 2004) compared to a physiological ratio of ∼1:50-100 (with actin concentration 25-72 uM (Gardel et al 2006)). Tighter F-actin bundles and decreased actin filament turnover are observed when the FLNA concentration is increased (Nakamura et al 2002;Schmoller et al 2009).…”
Section: Filamin Biomechanicsmentioning
confidence: 99%
“…Tissues and cellular networks are especially sensitive to external stresses [1][2][3][4][5][6][7] and a number of theoretical and simulation studies have attempted to gain an understanding of what controls the response of such systems to deformations [8,9]. Maxwell showed that there is a connectivity threshold z c , determined by the average coordination number of the network nodes, at which athermal networks of springs become rigid [10].…”
Section: Introductionmentioning
confidence: 99%